Vascular malformation of ileum: A possible cause of neonatal intestinal obstruction. (December 2020) - Singh, Gaurav; Banerjee, Rupa; Varma, Muni; Aggarwal, Satish K.; Gupta, Pallav
Abstract: Vascular lesions of gut are rare and they may rarely cause luminal obstruction in neonates. A baby boy born at 36 weeks of gestation presented with small bowel obstruction on day 3 of life. X-ray suggested small bowel obstruction. Contrast enema showed microcolon with multiple filling defects. Exploration revealed thin floppy gut with multiple segments of stenoses and dilatation with surface bluish discoloration but no perforation, two areas were resected. Proximal anastomosis was done and distally a stoma was formed. Histopathology showed vascular malformation in all the layers of gut. The diagnosis was impossible preoperatively and could be established after surgery only. Highlights: Vascular lesions of gut are very rare. They may cause luminal obstruction in neonates. X-ray suggested small bowel obstruction. Contrast enema shows microcolon with multiple filling defects due to the obstruction. The diagnosis is usually impossible preoperatively and can be established after surgery only.